Making the World of Difference: a service user-led education programme reshaping the learning environment in psychiatry. (April 2020) - Newton-Howes, Giles; Gordon, Sarah; Fedchuk, Dasha
Objective: To describe the implementation of a service user-led learning programme implemented within the education of undergraduate medical students and psychiatric registrars. Conclusion: This programme has the potential to impact on the learning of those early in their medical career and future consultant psychiatrists. Ongoing research will help to explain the reach and depth of the programme and the elements of greatest benefit.